[Gyula Andrássy 3]
vintage in Soltvadkert, wedding, shooting gallery, school-leaving ceremony (1973,1974, 1984), primary-school Páhi, boy in the swing, party with music, the Day of children's, excursion to Sopron, Fertőd, Nagycenk, Fertőrákos, cherry-picking, open-air bath, grandparents, Kecskemét 1989-1990 school-leaving ceremony, Torgyán arrives, flowers,